ANALISIS TRANSITIVITAS PADA ARTIKEL TENTANG PENGGUSURAN DI PULAU REMPANG OLEH PROJECT MULTATULI - Fitriana, Siti Labibah; Harras, Kholid Abdullah; Wiyanti, Sri (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2025)
Abstract This study aims to describe the discourse construction of eviction in Pulau Rempang, Riau Islands, as portrayed in the alternative media "Project Multatuli". The analysis is conducted using Halliday's transitivity approach and Fairclough's critical discourse analysis, employing a mixed-method approach (quantitative and qualitative). The research data consists of a news text titled "Mengubur Harapan Warga Rempang: Dulu Dijanjikan Sertifikat, Kini Digusur Demi Investasi Asing". The analysis results show that the text strongly aligns with the Rempang community. Halliday's transitivity analysis reveals the dominance of material processes (21 or 25.30% of findings), illustrating concrete actions of eviction and state violence. Additionally, circumstantial elements of place (196 or 54.44% of findings) indicate that the conflict is not only a social issue but also relates to politics and the struggle for living space. The discourse construction in the news text aligns with the values upheld by "Project Multatuli", namely democracy, humanity, social justice, equal rights, and environmental sustainability. Thus, this study reinforces the role of alternative media in amplifying marginalized voices and constructing resistance discourse against policies perceived as unjust.